Advanced-Stage Primary Cutaneous T-Cell Lymphoma Treated with Bexarotene and Denileukin Diftitox - Iván Cervigón-González; Luis Miguel Torres-Iglesias; Ángel Palomo-Arellano; Braulio Gil-Pascual (Karger Publishers, 2011)
Advanced-stage primary cutaneous T-cell lymphoma has an unfavorable prognosis and low survival rates. Aggressive treatment with chemotherapy is not curative and causes considerable side effects. The combination of bexarotene and denileukin diftitox is associated with an acceptable safety profile and a likely synergistic effect because bexarotene is capable of modulating expression of IL-2 receptor and enhance the susceptibility of T-cell leukemia cells to denileukin diftitox. In the case reported here, the response to this combined treatment was satisfactory and well tolerated. The patient showed a complete regression of pruritus, restlessness, and insomnia. Skin lesions improved partially, and lymphadenopathy was reduced and finally disappeared completely.